Modeling and experimental investigation of a Wurster type fluidized bed reactor coupled with an air atmospheric pressure plasma jet for the surface treatment of polypropylene particles. Issue 11 (20th August 2018) - Tabibian, Seyedshayan; Arefi‐Khonsari, Farzaneh; Anagri, Abdessadk; Leturia, Mikel; Moussalem, Antoine; Moscosa Santillan, Mario; Saleh, Khashayar; Touari, Yasmine; Pulpytel, Jerome
Abstract : Polypropylene (PP) particles are used for various purposes, however, the good mechanical properties of PP are counterbalanced by a poor wettability. The wettability of PP particles was therefore improved by an atmospheric pressure blown‐arc air plasma jet treatment in a new designed homemade Wurster fluidized bed reactor (Wurster‐FBR). This reactor, was used to treat 200 g of particles per batch. The surface free energy of PP particles determined by the Zisman method showed an increase from 30.7 to 38.6 mN m −1 after 120 s of treatment. XPS results showed a 5% increase of the atomic concentration of oxygen on the surface of the treated particles. In order to describe the process, a 2D axisymmetric non‐isothermal k‐ϵ turbulent model was used to determine the velocity field, pressure, and temperature profile of the gas phase inside the reactor. Furthermore an Eulerian‐Eulerian multiphasic CFD model was added to determine the dynamics of the particles inside the reactor, and the results were compared with fast imaging, thermocouple, and anemometry measurements. These investigations are very important to monitor the homogeneity of the particle treatments, to determine the average effective treatment time for each particle and to avoid overheating of thermally sensitive PP. Abstract : Experimental investigation and CFD numerical modeling of a fluidized bed reactor, coupled with an atmospheric pressure plasma jet are performed to improve the wettability of polymeric microparticles. The physical and chemical properties of non‐treated and plasma‐treated polypropylene particles are characterized by different methods such as XPS, SEM, and FT‐IR. Particles surface energy increase significantly after only 120 s treatment.